Effects of land and sea parameters on the dispersion of tweek atmospherics - Prasad R. (My University, 2025)
The appearance of tweeks on whistler sonograms has been discussed in terms of VLF wave propagation through the land-sea and ionospheric waveguide. It is shown that the conductivity of ground and sea mixed path, forming the lower surface of the waveguide, may provide an estimate of the source distance of whistlers generating atmospherics. © 1981.